Pengaruh Cognitive Style Dan Global Mindset Terhadap Manajemen Keuangan Pribadi Dan Pengaruh Manajemen Keuangan Pribadi Terhadap Intensi Berwirausaha - Peter Garlans Sina (Universitas Airlangga, 2013)
The aim of this research was to give a proof that the factors of style of thinking, global mindset, and personal finance management are the predictors for the entrepreneurial intentions. Through the distribution of questioners for 150 respondents, the results show that style of thinking and global mindset gave significant effects on personal finance management and it was also gave significant effect on entrepreneurial intentions. In the final section, the limitation of the research was also discussed which can be a follow-up by other researchers.